DUKUNGAN KELUARGA DENGAN KEKAMBUHAN PADA PASIEN SKIZOFRENIA - Febria Syafyu Sari (Jurnal Pembangunan Nagari, 2017)
Mental disorders are one of the public health problem in Indonesia. Social support is very important to the treatment and recovery of patients with mental disorders. Lack of family support is one factor that can influence the occurrence of relapse in patients with mental disorders. According to data from World Health Organization (2013), show the prevalence of schizophrenia is 450 million people wordwide. The purpose of this study is to look at the relationship of family support relationship with relapse in patients with schizophrenia in the Mental Hospital Polyclinic Dr. Achmad Mochtar Bukittinggi. This research uses descriptive correlational method using cross-sectional design. The study was conducted at Hospital Dr. Achmad Mochtar Bukittinggi in September 2016. The population in this study amounted to 1,628 people. Technique sampling is insidental sampling, with a sample of 70 people. Computerized data processing is done using SPSS with univariate and bivariate analysis, statistical test used was chi-square. Results of univariate analysis showed that (50.0%) of respondents showed a family of high family support, (48.6% )of patients experienced a relapse rarely. In bivariate analysis p value = 0.002 means there is a family support relationships with relapse of schizophrenia patients. Thus it is expected that the family should have a high knowledge about family support in order to avoid recurrence repeated in schizophrenic patients.